Provisional Notes on How âHilariousâ Living Under Sharia Law (The Case of Aceh) - Idria, Reza (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
AbstractDrawing upon anthropological theory of resistance and testing its limits, I will present a closer observation on how dissenting voices to the state project of Sharia in contemporary Aceh look on the ground. With-out thereby renouncing its violent effects, some ethnographic stories I recount in this writing will reveal how the implementation of Sharia in contemporary Aceh has created inherently amusing situations and how it has occasionally become a humor producing machine. Keywords: Sharia, Aceh, Political Humor, Postcolonial, Anthropology